TRAP1 downregulation in human ovarian cancer enhances invasion and epithelial-mesenchymal transition - Amoroso,MR; Matassa,DS; Agliarulo,I; Avolio,R; Lu,H; Sisinni,L; Lettini,G; Gabra,H; Landriscina,M; Esposito,F (Cell Death & Disease, 2016)
Ovarian cancer (OC) is the second leading cause of gynecological cancer death worldwide. Although the list of biomarkers is still growing, molecular mechanisms involved in OC development and progression remain elusive. We recently demonstrated that lower expression of the molecular chaperone TRAP1 in OC patients correlates with higher tumor grade and stage, and platinum resistance. Herein we show that TRAP1 is often deleted in high-grade serous OC patients (N=579), and that TRAP1 expression is correlated with the copy number, suggesting this could be one of the driving mechanisms for the loss of TRAP1 expression in OC. At molecular level, downregulation of TRAP1 associates with higher expression of p70S6K, a kinase frequently active in OC with emerging roles in cell migration and tumor metastasis. Indeed, TRAP1 silencing in different OC cells induces upregulation of p70S6K expression and activity, enhancement of cell motility and epithelial–mesenchymal transition (EMT). Consistently, in a large cohort of OC patients, TRAP1 expression is reduced in tumor metastases and directly correlates with the epithelial marker E-Cadherin, whereas it inversely correlates with the transcription factor Slug and the matrix metallopeptidases 2 and 9. Strikingly, pharmacological inhibition of p70S6K reverts the high motility phenotype of TRAP1 knock-down cells. However, although p70S6K inhibition or silencing reduces the expression of the transcription factors Snail and Slug, thus inducing upregulation of E-Cadherin expression, it is unable to revert EMT induced by TRAP1 silencing; furthermore, p70S6K did not show any significant correlation with EMT genes in patients, nor with overall survival or tumor stage, suggesting an independent and predominant role for TRAP1 in OC progression. Altogether, these results may provide novel approaches in OC with reduced TRAP1 expression, which could be resistant to therapeutic strategies based on the inhibition of the p70S6K pathway, with po